Bipolar spectrum, hypothyroidism, and their association with chronic fatigue/myalgic encephalomyelitis-like syndrome in long COVID: could they be identified as early determinants? - Tusconi, Massimo; Dursun, Serdar M.; Pegreffi, Francesco; Aviles Gonzalez, Cesar Ivan; Barrui, Vanessa; Fornaro, Michele; Hurtado Lujan, Luz Alba; Camacho Nunez, Lina Patricia; Vega Ochoa, Arley Denisse; Curcio, Felice; Carta, Mauro Giovanni; Cossu, Giulia (Frontiers in Psychiatry, 2025)
BackgroundLong COVID has been increasingly linked to persistent clinical manifestations, including chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME). However, the relationship between this syndrome and pre-existing conditions such as bipolar spectrum disorders and hypothyroidism is not yet clearly established. These disorders may influence the regulation of biorhythms and immune function, suggesting a possible role in the predisposition to the development of CFS/ME in the context of long-term COVID-19.ObjectivesThis study investigates the prevalence of hypothyroidism and bipolar spectrum disorders in patients with CFS/ME associated with long-term COVID-19. It compares it with pre-pandemic population data to determine whether these conditions may be predisposing factors.MethodsA case–control design was used to select cases from a clinical trial on CFS/ME in long COVID, while controls were extracted from pre-COVID epidemiological databases. Comparative statistical analyses, including chi-square tests and analysis of variance (ANOVA), were performed to assess significant differences in the frequency of these conditions between both groups.ResultsThe clinical sample showed significantly higher prevalence rates of hypothyroidism [27.78% vs. 1.14%; odds ratio (OR) = 33.07; 95% confidence interval (CI): 7.10–153.70] and bipolar spectrum disorders (16.67% vs. 0.2%; OR = 138.4; 95% CI: 36.40–526.43) compared to control populations (p < 0.0001 for both). Similarly, individuals screening positive for depressive symptoms (PHQ9 > 9) showed markedly increased odds (55.5% vs. 4.16%; OR = 28.75; 95% CI: 6.52–126.73).ConclusionThe findings suggest that hypothyroidism and bipolar spectrum disorders may act as predisposing factors in the development of CFS/ME in long-term COVID-19. Identifying these clinical antecedents could facilitate early detection and the development of targeted intervention strategies in at-risk populations.